NOTES ON FIMBRIBAMBUSA WIDJAJA, WITH A NEW SPECIES FROM THE LESSER SUNDA ISLANDS - Elizabeth Anita Widjaja (BRIN Publishing (Penerbit BRIN), 2020)
WIDJAJA, E. A. 2020. Notes on Fimbribambusa Widjaja, with a new species from the Lesser Sunda Islands. Reinwardtia 19(1): 55‒59. ‒‒ A new species, Fimbribambusa rifaiana Widjaja from Alor Island (Lesser Sunda Islands), is described and F. soejatmiae Widjaja & Ervianti, previously described contrary to Art. 40.7 of the ICN (2018), is validated. An improved generic concept of Fimbribambusa and an identification key to the Indonesian species are presented.